The Costa Rican Catholic Church, social justice, and the rights of workers, 1979-1996 - Sawchuk, Dana M. (Dana Marie), 1968- (Editions SR ;, 2004)
Provides a new understanding of the relationship between Church and State in 20th-century Costa Rica. Understanding the relationship between religion and social justice in Costa Rica involves piecing together the complex interrelationships between Church and State; between priests, popes, politics, and the people. This book does just that. Dana Sawchuk chronicles the fortunes of the country's two competing forms of labour organizations during the 1980s and demonstrates how different factions within the Church came to support either the union movement or Costa Rica's home-grown Solidarity movement. Challenging the conventional understanding of Costa Rica as a wholly peaceful and prosperous nation, and traditional interpretations of Catholic Social Teaching, this book introduces readers to a Church largely unknown outside Costa Rica. Sawchuk has carefully analyzed material from a multitude of sources: interviews, newspapers, books, and articles, as well as official Church documents, editorials, and statements by Church representativesto provide a firmly rooted socio-economic history of the experiences of workers, and the Catholic Church's responses to workers in Costa Rica.